2001
DOI: 10.1029/2000wr000002
|View full text |Cite
|
Sign up to set email alerts
|

Fate of herbicides in a shallow aerobic aquifer: A continuous field injection experiment (Vejen, Denmark)

Abstract: Abstract. A continuous, natural gradient, field injection experiment, involving six herbicides and a tracer, was performed in a shallow aerobic aquifer near Vejen, Denmark. Bentazone, (_+)-2-(4-chloro-2-methylphenoxy) propanoic acid (MCPP), dichlorprop, isoproturon, and the dichlobenil metabolite 2,6-dichlor-benzamide (BAM) were injected along with 2-methyl-4,6-dinitrophenol (not discussed in this paper) and the tracer bromide. The injection lasted for 216 days and created a continuous plume in the aquifer. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
50
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 22 publications
11
50
0
Order By: Relevance
“…No dichlorprop degradation was observed under aerobic conditions with any of the groundwater samples from the monitoring or drinking water abstraction wells ( Figure 2C). This persistence of dichlorprop is in accordance with the findings of Pedersen (2000) at an initial concentration of 50 µg L -1 under aerobic conditions, but it contrasts with the complete degradation of dichlorprop in a laboratory column experiment (Tuxen et al 2000) and a continuous field injection experiment (Broholm et al 2001) in an aerobic aquifer.…”
Section: Pesticide Mineralisation Potential In Groundwater Only Expersupporting
confidence: 78%
See 2 more Smart Citations
“…No dichlorprop degradation was observed under aerobic conditions with any of the groundwater samples from the monitoring or drinking water abstraction wells ( Figure 2C). This persistence of dichlorprop is in accordance with the findings of Pedersen (2000) at an initial concentration of 50 µg L -1 under aerobic conditions, but it contrasts with the complete degradation of dichlorprop in a laboratory column experiment (Tuxen et al 2000) and a continuous field injection experiment (Broholm et al 2001) in an aerobic aquifer.…”
Section: Pesticide Mineralisation Potential In Groundwater Only Expersupporting
confidence: 78%
“…Bentazone mineralisation was lower than 1% in all the groundwater samples from Well I and Well II, but this was higher than in the autoclaved control incubations (0.25%), thus indicating microbial mineralisation. Even though bentazone is usually considered to be recalcitrant in aquifers (Broholm et al, 2001), it was significantly removed at low concentrations in laboratory experiments with groundwater only. Thus, groundwater provides degradation potential.…”
Section: Pesticide Mineralisation Potential In Groundwater Only Expermentioning
confidence: 99%
See 1 more Smart Citation
“…In a natural gradient field injection experiment, a part of the Vejen aquifer (Denmark) was continuously exposed to herbicide concentrations of Ͻ40 g l Ϫ1 (8) (equivalent to Ͻ7 g kg Ϫ1 of sediment). After an initial lag phase of 80 to 100 days, fast degradation of mecoprop and dichlorprop was observed and herbicide concentrations decreased to below detection levels within the first meter from the injection wells (8). This indicated that the microbial community acclimated to the contamination.…”
mentioning
confidence: 84%
“…Within the NASRI project 7 retardation factors were determined during column experiments (Jekel, 2006, Licht et al, 2005. Referenced values for comparable conditions (sandy aquifer, low sedimentary organic carbon) are used for further 6 parameters (Braids, 2001, Broholm et al, 2001, Buss et al, 2006, Grischek et al, 1997, Heberer and Jekel, 2006, Jørgensen et al 1998, Mersmann et al, 2003, Scheytt et al, 2006, Stuyfzand et al, 2007, Tuxen et al, 2000. Eight retardation values are applied based on similarity considerations regarding the substances' structural characteristics (Table 2).…”
Section: Retardation Studymentioning
confidence: 99%